The Analysis of Protein Level and Amino Acid Profile in Eels (Anguilla marmorata (Q.) Gaimard and Anguilla bicolor) of Lake Poso - Jamaluddin; Nur Atina; Yonelian Yuyun (Journal of Pharmacy and Nutrition Sciences, 2019)
In this study used a sample of eel fish species Anguilla marmorata (Q.) Gaimard and Anguilla bicolor from Poso lake that has a high protein content and is a fish endemic to Central Sulawesi. These eels are consumed by the surrounding community of the lake, but the nutritional content remains unknown. The present research was aimed to determine the protein level and amino acid profile of Anguilla marmorata (Q.) Gaimard and Anguilla bicolor eels. The protein level testing used Kjeldahl method, and amino acid profile used High Performance Liquid Chromatography. The results demonstrate the protein level of the two samples Anguilla marmorata (Q.) Gaimard eels have a protein content of 41.84% and Anguilla bicoloreels at 33.75%. Anguilla marmorata (Q.) Gaimard and Anguilla bicolor eels contain 18 types of amino acid, comprised of 9 types of essential amino acids and 9 types of non-essential amino acids. Of the two samples of eel species Anguilla marmorata (Q.) Gaimard and Anguilla bicolor, have complete protein quality because it has all kinds of essential amino acids.